Respuestas
Respuesta dada por:
18
El método más simple lo brinda el álgebra de vectores.
OC = OA + 2 AB
AB = (2, - 2) - (- 3, 1) = (5, - 3)
OC = (- 3, 1) + 2 (5, - 3) = (7, - 5)
La respuesta es C(7, - 5)
Adjunto un gráfico.
Saludos Herminio
OC = OA + 2 AB
AB = (2, - 2) - (- 3, 1) = (5, - 3)
OC = (- 3, 1) + 2 (5, - 3) = (7, - 5)
La respuesta es C(7, - 5)
Adjunto un gráfico.
Saludos Herminio
Adjuntos:
![](https://es-static.z-dn.net/files/d17/b9c1ed44b1dc577888308bc606b0b697.jpg)
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años